Reliability of construction of nuclear power facilities in the global energy market (Nexo Revista Científica, 2021)
Purpose: development of conceptual provisions, methodical approaches and practical recommendations about modeling and integrated management at a pre-investment stage of nuclear power construction facilities in the international energy construction market. Materials and methods: a set of the interrelated methodological approaches based on the theory of complex systems life cycle, methods of abstraction, comparison, analysis, synthesis, opposition, modeling, forecasting, expert assessments, risk theory and others. The research is conducted with the use of open data resources of the International Energy Agency (IEA), International Atomic Energy Agency (IAEA), World Nuclear Association (WNA), Nuclear Energy Agency under OECD and ROSATOM State Corporation open statistical data. Results: Features of the modern global world market of nuclear power construction, as well as the role and place of Russia in it, are considered. A comprehensive review of the literature on the studied problems is accomplished. A methodology for modeling the organizational and economic reliability (OER) of complex systems is suggested. Modeling of the structural components of the life cycle (hereinafter LCi-j) of an investment project for the NPP construction on the international market in the conditions of high competition is proposed.